Fashion, Media, Promotion : the New Black Magic. - Sheridan, Jayne (Wiley, 2013)
In Fashion, Media, Promotion: the new black magic Fashion is linked to its communication networks - involving the reader in the process of selling Fashion in the global marketplace. Fashion's ingenuity in adapting to new means of promotion for digital and print media, websites, advertising, cinema, music and television, is celebrated. Hollywood's role in shaping Fashion's influence is assessed through Audrey Hepburn's persuasive iconography and the impact of the most watched movie of the 20th century: Gone with the Wind. Exceptional designers Coco Chanel, Christi.